Cardiac device related infective endocarditis in a patient with five pacemaker electrodes – diagnostic process and treatment - Domańska, Edyta; Witkowska, Anna; Kaliciński, Zygmunt; Drobiński, Dominik; Niewińska, Monika; Suwalski, Piotr; Kochmański, Marek; Suwalski, Kazimierz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Cardiac device related infective endocarditis (CDRIE) is a growing problem in daily practice. In the reported case, implantations of stimulation probes repeated over the years ended with the fifth. After planned extraction of a tooth, CDRIE with abundant vegetation on stimulation probes and inflammatory infiltration of the vena cava superior was observed. Surgical removal of the device was decided. On-pump beating heart stimulation probes were removed from heart ventricles. Simultaneously reconstruction of the vena cava superior and tricuspid valve plasty was performed. Postoperative course was uncomplicated. The patient presented atrial flutter about 70/min and did not require a pacemaker.